Neutron production in the interaction of 200-MeV deuterons with Li, Be, C, Al, Cu, Nb, In, Ta, and Au - Watanabe Yukinobu; Sadamatsu Hiroki; Araki Shouhei; Nakano Keita; Kawase Shoichiro; Kin Tadahiro; Iwamoto Yosuke; Satoh Daiki; Hagiwara Masayuki; Yashima Hiroshi; Shima Tatsushi; Nakayama Shinsuke (EPJ Web of Conferences, 2023)
Double-differential neutron production cross sections (DDXs) for 200-MeV deuteron induced reactions on Li, Be, C, Al, Cu, Nb, In, Ta, and Au were measured at forward emission angles ranging from 0° to 25° by means of a time of flight (TOF) method with EJ301 liquid organic scintillators. The measured DDXs were compared with JENDL-5 and TENDL-2021 nuclear data, and theoretical model calculations using DEURACS and PHITS codes. It was found that the JENDL-5 and DEURACS calculation are in better agreement with the measured DDXs than the PHITS calculation, while TENDL-2021 fails to reproduce both the spectral shape and magnitude of the measured DDXs for all the targets.